Overview: Application of Resin Waterproof Adhesive Materials in Bridge Deck Pavement in China. (20th March 2022) - Zhou, Lu; Zhang, Dan; Li, Xiaogang; Gao, Zhiwei; Chen, Qian; Wang, Chaohui
Abstract : To further promote the research and application of resin type waterproof adhesive layer materials, the types, relevant specifications, and research trends of resin type waterproof adhesive layer in China are comprehensively investigated. The performance evaluation indicators, performance requirement, and requirements in different specifications are systematically analyzed, and the key performance evaluation indicators are recommended. The basic properties of common resin type waterproof adhesive layer materials are studied, and the bonding properties of different resin waterproof adhesive layers were compared and evaluated. The results showed that pull-out strength, shear strength, tensile strength, elongation at break, low temperature flexibility, and impermeability are the key performance evaluation indicators of resin waterproof adhesive layer. The tensile property, corrosion resistance, and water impermeability of resin type waterproof adhesive layer material are good, the flexibility of epoxy resin type waterproof adhesive layer material is poor, and the flexibility of methyl methacrylate (MMA) waterproof adhesive layer material is good. The bonding performance of the epoxy resin waterproof adhesive layer is better than that of the MMA. As the temperature rises, the bonding performance of the two waterproof adhesive layers is significantly reduced. At 60°C, the average pull-out strengths of the epoxy resin and MMA waterproof adhesive layer were 1.83 MPa and 1.47 MPa, respectively.